Worshippers in Prussian Lithuania: The Scale of the Movement, Its Spread, and Its Image in the 1820s - Barasa, Darius (Senoji Lietuvos literatūra, 2018)
The historiography of surinkimai (private prayer and hymn-singing gatherings of Evangelical Lutherans in Prussian Lithuania) and worshippers was started in as early as the first half of the nineteenth century – as soon as the movement began spreading and became noticeable. Nonetheless, the movement of the surinkimininkai (people who attended such gatherings) in Prussian Lithuania has not been consistently researched: there exist gaps and white spots. First of all, the issue of the scale of the movement and of the network of the gatherings should be singled out. Based on the analysis of 1823 report of Karaliaučius consistory about religious associations functioning outside the Church in the districts of Karaliaučius and Gumbinė, the article attempts to adjust the data on the scale of the worshippers’ movement, its spread, and the image of the worshippers. The emergence of the report should be linked to the movement of the surinkimininkai, which became more active and numerous between 1818 and 1824. The central and province authorities made efforts to obtain multi-sided information on the movement and its participants in order to understand what kind of a movement it was, how dangerous and massive it was, and what measures had to be resorted to for its control. On the other hand, attention to sects and Pietist movements in the province of East Prussia might have sprung up due to the 1820 unrest that sparked in East Pomerania between the local authorities and one branch of the Pietist movement that had spread across that region. Very likely, this unpleasant experience stimulated gathering of information on similar Pietist movements active in the state that could cause unrest in the future. It was against the backdrop of such events that an instruction was issued in 1823 the aim of which was to record and keep watch on Pietist gatherings – in this particular case, worshippers – in the province of East Prussia. In the 1823 report, of 23 ecclesiastical inspections in Karaliaučius district only six parishes of three inspections, in which Pietist gatherings took place, were indicated. In Gumbinė district, over thirty were recorded in sixteen ecclesiastical inspections, but it was pointed out that in eight, or half of them, there were no religious associations. The majority of the latter were Masurian inspections, such as Ungura (Angeburg), Lukas (Lyck), Lėcius (Lötz), Johannisburg, Zėhesten (Seehesten), and others. The report provides data on the numbers of participants of the Pietist gatherings in individual parishes. Although the data is highly subjective and approximate, there were parishes with the largest and the smallest numbers of worshippers. In the parishes of Papelkiai, Jurbarkas, Ragainė, Viešvilė, Gilija, Skaisgiriai, and Lenkviečiai the numbers of the surinkimininkai were the highest. The smallest numbers were recorded in the parishes of Katniava, Pilkalnis, Malviškis, Geldapė, Šilėnai, and Žigupėnai. On the basis of the number of worshippers in individual parishes, it is possible to single out ecclesiastical inspections with the largest concentration of the gatherings. These were the ecclesiastical inspections of Ragainė, Naujoji, Labguva, Stalupėnai, and Įsrutis. Statistical calculations suggest that in the 1820s the surinkimininkai made up 2–4 per cent of the total population in the parishes of Prussian Lithuania. In the second half of the nineteenth century or at the turn of the twentieth century the surinkimininkai made up about a quarter, that is, around 25 per cent of the total population; thus, presumably, the Pietist movement was in the initial stage of formation in the 1820s and started gaining impetus during later years and decades. The 1823 report provides relevant information on the individuals who led worshippers’ gatherings in different parishes and the territorial boundaries of their activities. Nineteen preachers are mentioned in the report, and some of them have not been recorded in historiography. One of the most interesting and colourful parts of the report is the assessment of the worshippers and their activities. It should be noted that the image of the surinkimininkai given in the 1823 report is one of the earliest known in general. Therefore it is possible to trace how and to what extent this image was changing throughout the later century. Assessment of the worshippers largely depended on the clergymen’s individual attitudes. For instance, the superintendents of Labguva and Pakalnė (Ger., Niederung) expressed mostly negative opinions about the surinkimininkai; those of Gumbinė and Tilžė were indifferent, while the superintendents of Klaipėda, Geldapė, Ragainė, and especially of Įsrutis, were positive about them. The results of the 1823 document show that research into the nineteenth-century surinkimininkai movement in Prussian Lithuania is promising, especially when the opportunities offered by yet undiscovered archival documents are exploited.